Pupuk Kandang Sapi dan Pupuk Organik Cair Buah Busuk Terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Vigna radiata L.) - Erlita Erlita; Iwan Hasrizart (Jurnal Agrofolium, 2024)
Cattle Manure and Rotten Fruit Liquid Organic Fertilizer on the Growth and Production of Green Beans (Vigna radiata L.) The aim of the study was to determine the application of cow manure and rotten fruit liquid organic fertilizer and their interactions on the growth and production of green beans (Vigna radiata L) ”. The research was conducted in Kedai Damar Village, Tebing Tinggi District, Serdang Bedagai District, North Sumatra Province. Held in December 2022 s.d. April 2023. This study used Factorial RAK with 2 factors studied with 3 repetitions. The first factor was cow manure (K) consisting of 4 levels, namely K0 = no treatment (control), K1 = 4 kg per plot, K2 = 8 kg per Plot, K3 = 12 kg per Plot. The second factor was rotten fruit liquid fertilizer (C), which consisted of 4 levels, namely C0 = no treatment (control), C1 = 25 ml liter-1 of water, C2 = 50 ml liter-1 of water, C3 = 75 ml liter-1 of water. The results showed that the application of cow manure had a very significant effect on the parameters of the number of pods per sample, the number of pods per plot, the weight of 100 seeds per sample and the weight of 100 seeds per plot. The application of rotten fruit liquid organic fertilizer had a significant effect on the weight parameter of 100 seeds per sample. While the interaction has a very significant effect on the weight parameter of 100 seeds per sample and has a significant effect on the number of leaves parameter